2020
DOI: 10.1002/jmv.25862
|View full text |Cite
|
Sign up to set email alerts
|

Clinical performance of Determine HBsAg 2 rapid test for Hepatitis B detection

Abstract: Hepatitis B virus (HBV) infection is estimated to affect 292 million people worldwide, 90% of them are unaware of their HBV status. The Determine HBsAg 2 (Alere Medical Co, Ltd Chiba Japan [Now Abbott]) is a rapid test that meets European Union (EU) regulatory requirements for Hepatitis B surface antigen 2 (HBsAg) analytical sensitivity, detecting the 0.1 IU/mL World Health Organization (WHO) International HBsAg Standard. This prospective, multicentre study was conducted to establish its clinical performance. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…This kit detected HBs-IS at a concentration of 0.1 IU/mL and tested positive for all positive RRP specimens. These results indicated that Determine2 has equivalent sensitivity to that of automated HBsAg kits and can be used in screening for HBV infections in low-resource settings [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…This kit detected HBs-IS at a concentration of 0.1 IU/mL and tested positive for all positive RRP specimens. These results indicated that Determine2 has equivalent sensitivity to that of automated HBsAg kits and can be used in screening for HBV infections in low-resource settings [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…A simple rapid test (Alere Determine HBsAg; Alere Medical Co. Ltd., Chiba, Japan) with a fingerstick whole-blood sensitivity and specificity of 97.2% and 98.5%, respectively, 11 was used instead of the traditional ELISA test because it is better suited for field use. Testing for HBsAg was performed according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Importantly, point-of-care (POC) testing tools are being developed and used to more easily diagnose HBV. Through these tests, the diagnostic process can start to move away from established healthcare settings, aiding diagnosis in resource-poor locations and high-risk communities (42). Despite these advancements, hepatitis infection is still largely underdiagnosed, with approximately 80% of HBV and HBC cases remaining unidentified.…”
Section: Diagnosismentioning
confidence: 99%